2013
DOI: 10.1002/polb.23265
|View full text |Cite
|
Sign up to set email alerts
|

Vertical confinement and interface effects on the microstructure and charge transport of P3HT thin films

Abstract: Using X-ray diffraction-based pole figures, we present quantitative analysis of the microstructure of poly(3-hexylthiophene) thin films of varying thicknesses, which allows us to determine the crystallinity and microstructure at the semiconductor-dielectric interface. We find that the interface is approximately one fourth as crystalline as the bulk of the material. Furthermore, the use of a self-assembled monolayer (SAM) enhances the density of interface-nucleated crystallites by a factor of $20. Charge transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
146
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 92 publications
(158 citation statements)
references
References 53 publications
9
146
3
Order By: Relevance
“…13,17,66,[69][70][71][72] As mentioned above, the structural and optical analyses are bulk measurements, whereas transport measurements in the context of OTFTs is far more sensitive to the polymer order and conformation at the interface. 11 Since surface functionalization has an enhancing effect limited to within approximately 10 nm of the modified interface, 11,40 we speculate that the measured improvements in local order averaged over the entire film depth may be even more pronounced at the interface, perhaps explaining the dramatic enhancement of carrier mobility by nearly two orders of magnitude.…”
Section: Local Order In P3ht Filmsmentioning
confidence: 99%
See 4 more Smart Citations
“…13,17,66,[69][70][71][72] As mentioned above, the structural and optical analyses are bulk measurements, whereas transport measurements in the context of OTFTs is far more sensitive to the polymer order and conformation at the interface. 11 Since surface functionalization has an enhancing effect limited to within approximately 10 nm of the modified interface, 11,40 we speculate that the measured improvements in local order averaged over the entire film depth may be even more pronounced at the interface, perhaps explaining the dramatic enhancement of carrier mobility by nearly two orders of magnitude.…”
Section: Local Order In P3ht Filmsmentioning
confidence: 99%
“…11 Importantly it has been suggested that surface functionalization has an enhancing effect on interfacial order, with the effect limited to within approximately 10 nm of the modified interface, 11,40 which means that the increased molecular order of polymer film at the interface with the OTS-treated substrate may arise from the increased interfacial order in very thin (less than ca. 10 nm) P3HT layer.…”
Section: Otft Device Performancementioning
confidence: 99%
See 3 more Smart Citations